Variasi Bahasa Melayu Dialek Kapuas Hulu pada Mahasiswa UPGRI Pontianak - Fitri Wulansari; Emelda Ariyanti; Salma Salma; Nesya Exleria; Agasta Mardela (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: This study aims to describe the linguistic variation of the Kapuas Hulu Malay dialect used by students of the English Language Education Study Program at Universitas PGRI Pontianak as a form of sociolinguistic identity in higher education. The background of this research is the limited studies examining the use of the Kapuas Hulu Malay dialect in academic settings, particularly in multilingual interactions among students. This research employed a qualitative descriptive approach with an ethnography of communication method. Data were collected through participatory observation, speech recording, and in-depth interviews with two students who are native speakers of the Kapuas Hulu dialect. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings reveal that the linguistic variations occur at the phonological, lexical, and syntactic levels, along with phenomena of code-switching, code-mixing, and language interference in both formal and informal communication. The use of the dialect functions as a marker of social and cultural identity as well as an adaptive communication strategy within the academic environment. Therefore, the Kapuas Hulu Malay dialect remains actively used and plays an important role in students’ communication practices in higher education.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan variasi bahasa Melayu dialek Kapuas Hulu yang digunakan oleh mahasiswa Program Studi Pendidikan Bahasa Inggris Universitas PGRI Pontianak sebagai bentuk identitas sosiolinguistik dalam konteks pendidikan tinggi. Latar belakang penelitian ini didasarkan pada terbatasnya kajian mengenai penggunaan dialek Melayu Kapuas Hulu di lingkungan akademik, khususnya dalam interaksi mahasiswa pada situasi multibahasa. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode etnografi komunikasi. Data dikumpulkan melalui teknik observasi partisipatif, perekaman tuturan, dan wawancara mendalam terhadap 2 mahasiswa yang merupakan penutur asli dialek Kapuas Hulu. Analisis data dilakukan menggunakan model interaktif Miles, Huberman, dan Saldaña yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa variasi bahasa yang ditemukan mencakup aspek fonologis, leksikal, dan sintaksis, serta terdapat fenomena alih kode, campur kode, dan interferensi bahasa daerah dalam komunikasi formal maupun informal. Penggunaan dialek tersebut berfungsi sebagai penanda identitas sosial dan budaya sekaligus sebagai strategi komunikasi adaptif dalam lingkungan akademik. Dengan demikian, dialek Melayu Kapuas Hulu tetap eksis dan memiliki peran penting dalam dinamika komunikasi mahasiswa di perguruan tinggi.